Long noncoding RNA SNHG14 regulates ox-LDL-induced atherosclerosis cell proliferation and apoptosis by targeting miR-186-5p/WIPF2 axis. (January 2021) - Tao, Z; Cao, Z; Wang, X; Pan, D; Jia, Q
To investigate the role of small nucleolus RNA host gene 14 (SNHG14) in the progression of atherosclerosis (AS), bioinformatics analysis, and other relevant experiments (cell counting kit-8, flow cytometry, quantitative real-time polymerase chain reaction, luciferase reporter, RNA immunoprecipitation, RNA pull-down, and western blot assays) were done. The current study revealed that SNHG14 level was high in the serum of AS patients and oxidized low-density lipoprotein (ox-LDL)-induced AS cell lines. Besides, we found that SNHG14 accelerated cell proliferation while inhibited cell apoptosis in ox-LDL-induced AS cell lines. Next, SNHG14 was confirmed to be a sponge for miR-186-5p in AS cells, and it was validated that SNHG14 regulated AS cell proliferation and apoptosis by sponging miR-186-5p. Moreover, we uncovered that WAS-interacting protein family member 2 (WIPF2) was a downstream target of miR-186-5p in AS cells. Finally, it was demonstrated that miR-186-5p modulated AS cell proliferation and apoptosis via targeting WIPF2. To conclude, our research disclosed that SNHG14 affected ox-LDL-induced AS cell proliferation and apoptosis through miR-186-5p/WIPF2 axis, which may provide a theoretical basis for the treatment and diagnosis of AS.